Meaning Relationship of the Verb Hope and Wish in English - Carla Maretha (SIGEH ELT : Journal of Literature and Linguistics, 2021)
This research is qualitative which aims to describe grammatical form of wish and hope, to classify elements of wish and hope sentences, and to analyse meaning of both words based on meaning tendency of grammatical form and elements. This research uses British National Corpus as data source, then the data are presented informally. This research shows that hope and wish have the same 5 grammatical forms, but hope and wish cannot be used interchangeable for having different tendency. Hope and wish can be synonymous conceptually, but characteristically they cannot be (real-unreal, and desired-wanted).